Assistência pré-natal no contexto da pandemia da covid-19: olhares de gestantes e enfermeiros da Atenção Primária à Saúde - Dias, Francisca Isaelly dos Santos (2022)
SARS-CoV-2 was first identified in Wuhan, China, in December 2019, starting an outbreak. The high rate of infectivity of this virus associated with morbidity and mortality generated a global health crisis and on March 11, 2020, the World Health Organization declared a andemic of this new disease, called COVID-19.The study aims to understand prenatal care in the context of COVID-19. 19 in the city of Sobral - CE, from the perspective of pregnant women and nurses in Primary Health Care. This is an exploratory-descriptive study with a qualitative approach. The research participants were nurses who work at the Family Health Centers, at the headquarters, in the Municipality of Sobral-CE, and women enrolled in the territories of the aforementioned CSFs who were pregnant from March/2020 to February/2022. Data collection took place between July 2021 and March 2022, with semi- structured interviews in person and/or online. For the analysis of information, Bardin's content analysis was adopted. The study was submitted to the Research Ethics Committee (CEP) of the UniversidadeEstadual Vale do Acaraú (UVA), respecting ethical principles, considering Resolution 466/12 of the National Health Council. From the analysis of the narratives, two final categories and seven subcategories emerged. The following final categories are: Emotional tensions and their repercussions on prenatal care during a pandemic; and Reorganization of the work process for health care for pregnant women. Thus, the research provided to know the experiences lived by nurses and pregnant women in relation to prenatal care during the COVID-19 pandemic, as well as the main changes that occurred in prenatal care within the scope of PHC. In addition to the biological, psychological, emotional and social impacts that the pandemic caused.